Drug Resistance Mechanisms of Mycoplasma pneumoniae to Macrolide Antibiotics. (28th January 2014) - Liu, Xijie; Jiang, Yue; Chen, Xiaogeng; Li, Jing; Shi, Dawei; Xin, Deli
Abstract : Throat swabs from children with suspected Mycoplasma pneumoniae ( M. pneumoniae ) infection were cultured for the presence of M. pneumoniae and its species specificity using the 16S rRNA gene. Seventy-six M. pneumoniae strains isolated from 580 swabs showed that 70 were erythromycin resistant with minimum inhibitory concentrations (MIC) around 32–512 mg/L. Fifty M. pneumoniae strains (46 resistant, 4 sensitive) were tested for sensitivity to tetracycline, ciprofloxacin, and gentamicin. Tetracycline and ciprofloxacin had some effect, and gentamicin had an effect on the majority of M. pneumoniae strains. Domains II and V of the 23S rRNA gene and the ribosomal protein L4 and L22 genes, both of which are considered to be associated with macrolide resistance, were sequenced and the sequences were compared with the corresponding sequences in M129 registered with NCBI and the FH strain. The 70 resistant strains all showed a 2063 or 2064 site mutation in domain V of the 23S rRNA but no mutations in domain II. Site mutations of L4 or L22 can be observed in either resistant or sensitive strains, although it is not known whether this is associated with drug resistance.